2021
DOI: 10.1089/cyber.2020.0253
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Stalking, Cyber Harassment, and Adult Mental Health: A Systematic Review

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 43 publications
3
55
0
3
Order By: Relevance
“…For example, there is a reasonably clear pattern that victims of psychosocial cybercrimes such as revenge porn and cyberbullying directly and primarily experience a range of similar emotional, psychological, and behavioural health consequences, according to multiple comprehensive review articles on four psychosocial cybercrime types included in this present study: (see (i) Walker & Sleath's (2017) review of 82 published works on revenge porn; (ii) Watts et al.’s (2017) review of 54 published articles on cyberbullying; and (iii) Stevens, Nurse & Arief's (2021) review of 43 articles on cyberstalking and online harassment for fuller analyses). These consequences include anxiety, self‐harming, depression, low self‐esteem, and suicidal ideation to varying degrees (Stevens, Nurse & Arief, 2021; Walker & Sleath, 2017; Watts et al., 2017). However, in addition to the direct psychological costs of psychosocial cybercrimes, coping with these psychologically based crimes can have indirect financial consequences.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a reasonably clear pattern that victims of psychosocial cybercrimes such as revenge porn and cyberbullying directly and primarily experience a range of similar emotional, psychological, and behavioural health consequences, according to multiple comprehensive review articles on four psychosocial cybercrime types included in this present study: (see (i) Walker & Sleath's (2017) review of 82 published works on revenge porn; (ii) Watts et al.’s (2017) review of 54 published articles on cyberbullying; and (iii) Stevens, Nurse & Arief's (2021) review of 43 articles on cyberstalking and online harassment for fuller analyses). These consequences include anxiety, self‐harming, depression, low self‐esteem, and suicidal ideation to varying degrees (Stevens, Nurse & Arief, 2021; Walker & Sleath, 2017; Watts et al., 2017). However, in addition to the direct psychological costs of psychosocial cybercrimes, coping with these psychologically based crimes can have indirect financial consequences.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the flip side, comprehensive reviews of published studies on psychosocial cybercrime types tell a different story. For example, Walker & Sleath's (2017) review of 82 published works on revenge porn, Watts et al.’s (2017) review of 54 published articles on cyberbullying, and Stevens, Nurse & Arief's (2021) review of 43 articles on cyberstalking and online harassment suggest that victims of this psychosocial cybercrime category were primarily targeted on the basis of their gender. This article aims to illustrate that psychosocial cybercrimes are more gendered than socio‐economic cybercrimes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The term “cyberbullying” itself is not standardized with researchers using a variety of alternate terms including “online bullying/harassment,” “cyber-aggression,” and others, leading to some confusion with actual instances of cyber stalking and cyber harassment [ 3 ]. While cyberbullying was viewed as an extension of bullying practices with different means, its definition has also been contested and revisited continuously, with a conciliatory proposal put forward by Tokunaga [ 4 ] who defined cyberbullying as “any behavior performed through electronic or digital media by individuals or groups that repeatedly communicates hostile or aggressive messages intended to inflict harm or discomfort on others,” emphasizing the intrusion into personal space.…”
Section: Introductionmentioning
confidence: 99%
“…The term "cyberbullying" itself is not standardized with researchers using a variety of alternate terms including "online bullying/harassment," "cyber-aggression," and others, leading to some confusion with actual instances of cyber stalking and cyber harassment [3]. While cyberbullying was viewed as an extension of bullying practices with different means, its definition has also been contested and revisited…”
Section: Introductionmentioning
confidence: 99%
“…17 It not only undermines the victims' autonomy, identity, dignity, and wellbeing 18 but also has significant and long-lasting psychosexual consequences. A recent meta-analysis 19 reported that victims of cyber stalking and/or harassment experienced a multitude of harmful and detrimental consequences for their mental health, including depression, anxiety, suicidal ideation, and panic attacks. Similarly, experiences of cyber-sexual violence were found to be associated with symptoms of depression, anxiety, stress, and posttraumatic reactions.…”
Section: Introductionmentioning
confidence: 99%